Do night and around-the-clock firefighters' shift schedules induce deviation in tau from 24 hours of systolic and diastolic blood pressure circadian rhythms?. (14th September 2017) - Reinberg, Alain E.; Smolensky, Michael H.; Riedel, Marc; Riedel, Cedric; Brousse, Eric; Touitou, Yvan
ABSTRACT: Systolic (S) and diastolic (D) blood pressures (BP) [SBP and DBP] are circadian rhythmic with period (τ) in healthy persons assumed to be maintained at 24.0h. We tested this assumption in a sample of 30 healthy career (mean >12 yrs) 30-to-46 yr-old male Caucasian French firefighters (FFs) categorized into three groups according to work schedule and duties: Group A – 12 FFs working 12h day, 12h night, and occasionally 24h shifts and whose primary duties are firefighting plus paramedical and road rescue services; Group B – 9 FFs working mostly 12h day and 12h night shifts and whose duties are answering incoming emergency calls and coordinating service vehicle dispatch from fire stations with Group A personnel; Group C – 9 day shift (09:00–17:00h) FFs charged with administrative tasks. SBP and DBP, both in winter and in summer studies of the same FFs, were sampled by ambulatory BP monitoring every 1h between 06:00–23:00h and every 2h between 23:01–05:59h, respectively, their approximate off-duty wake and sleep spans, for 7 consecutive days. Activity (wrist actigraphy) was also sampled at 1-min intervals. Prominent τ of each variable was derived by a power spectrum program written for unequal-interval time series data, and between-group differences in incidence of τ≠24h of FFs were assessed by chi square test. Circadian rhythm disruption (τ≠24h) of either the SBP or DBP rhythm occurred almost exclusively in night and 24h shift FFs of Group A and B, but almost never in day shift FFs of Group C, and it was not associated with altered τ from 24.0h of the circadian activity rhythm. In summer, occurrence of τ≠24 for FFs of Group A and B differed from that for FFs of Group C in SBP ( p =0.042) and DBP ( p =0.015); no such differences were found in winter ( p >0.10). Overall, manifestation of prominent τ≠24h of SBP or DBP time series was greater in summer than winter, 27.6% versus 16.7%, when workload of Group B FFs, i.e. number of incoming emergency telephone calls, and of Group A FFs, i.e. number of dispatches for provision of emergency services, was, respectively, two and fourfold greater and number of 12h night shifts worked by Group B FFs and number of 24h shifts worked by Group A FFs was, respectively, 92% and 25% greater. FFs of the three groups exhibited no winter-summer difference in τ≠24h of SBP or SDP; however, τ≠24h of DBP in Group B FFs was more frequent in summer than winter ( p =0.046). Sleep/wake cycle disruption, sleep deprivation, emotional and physical stress, artificial light-at-night, and altered nutrient timings are hypothesized causes of τ≠24h for BP rhythms of affected Groups A and B FFs, but with unknown future health effects.